Spinal Cord Compression due to Extra Medullary Hematopoiesis in a Case Of Thalassemia Minor: A Rare Case Report - Patil, Purwa Rangrao; Rajpurkar, Samruddhi Dilip; Sisodia, Shantilal M; Patil, Ajinky Ashok; Ahuja, Sanjana (Annals of Pathology and Laboratory Medicine, 2018)
Extra medullary Hematopoiesis occurs as a result of inefficient erythropoiesis in several conditions. Para spinal Involvement is rare and it produces morbid consequences due to spinal cord compression. We present a very rare case of patient with Thalassemia Minor having Extra medullary Hematopoiesis causing Spinal cord compression followed by a detailed review of literature regarding the clinical, radiological and pathological features and treatment modalities of Extra medullary Hematopoiesis affecting predominantly the spinal region in patients with Thalassemia.